Evaluation of quality and safety of cow and goat milk from Escherichia coli O157 and Campylobacter spp - Nordin, Yusralimuna (2018)
High demand for milk has been observed amongst the Malaysian public. Hence, research in milk is essential to assure food safety in milk consumption. This study evaluates the quality of locally-produced milk and present of bacterial hazards in cow and goat milk. A total of 120 milk samples (30 raw cow milk, 30 pasteurised cow milk, 30 raw goat milk and 30 pasteurised goat milk) were collected from dairy farms, delivery milkman, marts and markets in Selangor. The sampling has been carried out from May 2016 until August 2017. The bacteriological quality of milk was evaluated for the presence of mesophilic, coliform and Escherichia coli bacteria. An acceptable standard limit of < 1 X 105 CFU/ml for the total bacterial count was used to indicate good quality of milk. The standard is according to Malaysian Food Act 1983 and Food regulations 1985. Additionally, the bacteriological safety of milk was assessed. The selected pathogenic E. coli O157 and Campylobacter species were identified using most-probable number and polymerase chain reaction (MPN-PCR) for quantification and species identification. The behaviour of E. coli O157 also has been investigated in this study. The E. coli O157 counts were evaluated over 24 hours of incubation at different temperatures. Overall, all type of milks exceeded 100,000 CFU/ml. Approximately half of milk samples were contaminated with coliform bacteria. A proportion has exceeded the acceptable limit of 50 CFU/ml. The presence of E. coli was detected in over 44% of samples. Further screening detected pathogenic E. coli O157 in 10 samples (raw cow milk 13.33%; other type of milks 6.67%). Campylobacter spp. were not detected in samples. In addition, E. coli O157 was able to survive and proliferate at refrigerated and ambient temperature. The presence of pathogenic E. coli O157 in milk signify a threat to public health. The finding is expected to aid the risk profile for E. coli O157 as there is no complete data available for assessment of the microbiological quality.